1997
DOI: 10.1088/0022-3727/30/18/002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of imaging conditions on the appearance of lattice-resolved AFM images of mica surfaces

Abstract: The effect of imaging environments and imaging parameters on the lattice-resolved AFM images of mica surfaces has been investigated. As the force-contrast of an AFM image is determined by the tip - surface interactions, the appearance of the AFM images changes accordingly when the force applied to the tip, the scanning direction, or the imaging liquid used is changed. All these factors can modify the details of the tip - surface contact situation so as to affect both the vertical repulsive and the direction-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
3
5
0
Order By: Relevance
“…First, many AFM experiments of muscovite surfaces with different atmospheres show dot-like patterns in the presence of the water. The representative experiments of Liu et al using contact mode AFM demonstrated that the observed patterns varied with the overlying liquid . When n -decanol was used as the overlying liquid, the pattern was honeycomb-like, whereas the dot-like pattern was obtained with water as the overlying liquid.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…First, many AFM experiments of muscovite surfaces with different atmospheres show dot-like patterns in the presence of the water. The representative experiments of Liu et al using contact mode AFM demonstrated that the observed patterns varied with the overlying liquid . When n -decanol was used as the overlying liquid, the pattern was honeycomb-like, whereas the dot-like pattern was obtained with water as the overlying liquid.…”
Section: Resultsmentioning
confidence: 99%
“…We will now discuss how the simulation results will aid in interpreting AFM experiments. It has been suggested that the first hydration layer gives dot-like ,,, and honeycomb-like patterns , in AFM images. First, many AFM experiments of muscovite surfaces with different atmospheres show dot-like patterns in the presence of the water.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are only a few AFM studies of mica cleaved and maintained in vacuum (UHV) and these investigated lateral forces and friction, and include Friction Force Microscopy (FFM) images involving stick-slip interactions, which gave insufficient resolution to distinguish the atomic lattice [39; 40]. The periodicity of the mica lattice can also be resolved in air by FFM [41; 42], and it is consistent with the expected unit cell dimensions of mica [43]. Sometimes, the very large attractive forces in air due to van der Waals and capillary interactions mean that significant damage can occur as the tip is dragged across the surface, resulting in a loss of lateral resolution.…”
Section: The Surface Structure Of Cleaved Mica and The Exchange Of Sumentioning
confidence: 86%